Cancer Prevalence Trend in Central Region of Nepal - Khan, Gulam Muhammad; Thappa, RK; Adhikari, DS; Rajbhandari, M; Dwa, P; Shrestha, S; Oli, S (Journal of Chitwan Medical College, 2013)
Cancer is a multi-cellular disease that causes excessive proliferation of cells. In this study, our objective was to determine the epidemiological distribution patterns for different types of cancer. A retrospective cross-sectional descriptive study was conducted. A modified data collection form was used to collect the information regarding religion, ethnicity, sex and district. A total of 240 cancer patients were included in the study. Majority (83.33%) of cancer patients were Hindus and among them Newars were the most affected ones with 30.42% prevalence. The gender wise distribution presents that females were highly affected by cancer than males. Within male patients, respiratory and digestive cancers were highly prevalent with 50.53% and 30.53% respectively. When respiratory cancer cases were further studied, lung cancer constituted the most cases with 60.42% cases. In case of female patients, reproductive and respiratory cancers were most prevalent with 62.07% and 14.48% cases respectively. Among reproductive cancers, breast cancer was highly prevalent with 45.56% cases and the susceptible age group for this was 40-50 yrs. The district wise distribution presented that mostly patients were from Kathmandu, Lalitpur, Bhaktapur and Sindhupalchowk districts. Findings from current study revealed that cancer cases in both males and females were common but females were highly prone to reproductive cancer whereas males were prone to respiratory cancer. Continual future research on cancer trends is warranted to study the actual cancer scenario. Journal of Chitwan Medical College 2013; 3(1): 22-25 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8461